2019
DOI: 10.1101/863605
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural Brain Alterations and Their Association with Cognitive Function and Symptoms in Attention-Deficit/Hyperactivity Disorder Families

Abstract: AbstractGray matter disruptions have been found consistently in Attention-deficit/Hyperactivity Disorder (ADHD). The organization of these alterations into brain structural networks remains largely unexplored. We investigated 508 participants (281 males) with ADHD (N = 210), their unaffected siblings (N = 108), individuals with subthreshold ADHD (N = 49), and unrelated healthy controls (N = 141) with an age range from 7 – 18 years old from 336 families in the Dutch NeuroIMAGE p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Recently, we leveraged structural magnetic resonance imaging (sMRI) data from reasonable large adult and adolescent samples to study brain alterations underlying persistent ADHD symptoms and cognitive impairments using consistent analytical approaches. We identified that GMV of the superior/middle/inferior frontal regions was consistently associated with working memory performance, and cerebellum GMV was consistently related to inattention symptoms in both adults and adolescents with ADHD [22,28,36]. Our findings emphasize that not only the symptom and impaired cognitive functions but also the underlying neurological alterations persist from childhood to adulthood in individuals with ADHD.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Recently, we leveraged structural magnetic resonance imaging (sMRI) data from reasonable large adult and adolescent samples to study brain alterations underlying persistent ADHD symptoms and cognitive impairments using consistent analytical approaches. We identified that GMV of the superior/middle/inferior frontal regions was consistently associated with working memory performance, and cerebellum GMV was consistently related to inattention symptoms in both adults and adolescents with ADHD [22,28,36]. Our findings emphasize that not only the symptom and impaired cognitive functions but also the underlying neurological alterations persist from childhood to adulthood in individuals with ADHD.…”
Section: Introductionmentioning
confidence: 55%
“…Converging evidence from anatomical studies suggest that children/adolescents with ADHD have global gray matter volume (GMV) reductions [11][12][13][14][15] and regional GMV reductions in the basal ganglia [12,[16][17][18], the frontal lobe [13,[18][19][20], the anterior cingulate cortex [21], and the cerebellum [11,14,18,22]. Adults with ADHD also showed reduced total (cortical) GMV [23][24][25], reduced GMV in the frontal lobe [23,[25][26][27][28], caudate nucleus [29,30], and cingulate cortices [16,25,27,31], but the reduction is less conclusive as the recent ENIGMA-ADHD studies revealed no significant ADHD versus control differences for adults [32,33].…”
Section: Introductionmentioning
confidence: 99%